(untitled) (Orfeu, 2018)
This article comes from the research I developed in the Masters in Music at the Universidade do Estado de Santa Catarina (UDESC), which dealt with the meanings attributed to the practice of the blues at Caxias do Sul (RS) and, above all, the vocal practices linked to this musical genre. I try to understand how the voice is constructed from identity values, gender issues and racialization. Therefore, I aim to discuss, from the ethnographic experience, since August 2017 to January 2018, the voice in performance as a means of deconstructing norms and binarisms linked to vocal know-how.